SISTEM INFORMASI PENGOLAHAN DATA PENANGANAN KASUS KLIEN PADA LAW OFFICE SUJIARNO BROTO AJI (Information Technology and Telematics, 2015)
Abstrak Law Office SujiarnoBrotoAji is a law office, lawyers, legal consultant who handles cases related to other legal matters civil and criminal, lawyer or legal consultant can mean someone who does or advises and represents for the defense or any other person associated with the settlement of a legal case. Goal to be achieved isto create a system of data goverhance Law Office SujiarnoBrotoAji can be used to perform data processing of computerized case management clients to more quickly and accurately so that to facilitate the handle of the case of the client Law Office SujiarnoBrotoAji. The result of this research the system of processing andhandling client information on Law Office SujiarnoBrotoAji can be used to perform data processing of computerized case management client in order to more quickly and accurately so that to facilitate the handle of the case of the client Law Office SujiarnoBrotoAji so that reduce error that usually occur in manual system.   Keywords: system informationKlien, Law Office Sujiarno Broto Aji